A highly fluorescent post-modified metal organic framework probe for selective, reversible and rapid carbon dioxide detection. (January 2020) - Tang, Yilong; Chen, Jinming; Wu, Huafeng; Yu, Jinping; Jia, Jinlan; Xu, Wei; Fu, Yanyan; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract: The monitoring of the arterial and exhaled CO2 is of great importance. Despite of many reports on metal organic frameworks (MOFs) in adsorbing and separating CO2, the application of fluorescent MOFs probes for CO2 detection was rarely reported. A new fluorescent MOF probe UIO-66-ONa for CO2 detection was developed via post-synthesis of UIO-66-NH2 through a Schiff base reaction with salicylaldehyde and further treatment with sodium hydroxide. This probe exhibited a remarkable fluorescence color change from green to blue and showed excellent sensitivity and selectivity for CO2 sensing in solution. The detection limit was as low as 3.5 × 10 −7  M. The excellent sensing performance of UIO-66-ONa was ascribed to the efficient reaction between sodium phenolic group and CO2, which led to the transformation of UIO-66-ONa to UIO-66-OH as evidenced by the emission spectra. This post-synthetic modification idea provided a new strategy for designing fluorescent MOFs probes for CO2 detection. Graphical abstract: A new fluorescent metal organic framework probe (UIO-66-ONa) exhibits the excellent sensing performance towards CO2 detection as the interaction between sodium phenolic group and CO2, the detection limit is 3.5 × 10 −7  M.Image 1 Highlights: A new fluorescent MOF probe (UIO-66-ONa) for CO2 detection was developed via post-synthesis of UIO-66-NH2. UIO-66-ONa exhibits excellent selectivity, sensitivity and reusability for CO2 detection in solution. A promising design strategy for the synthesis of high efficient fluorescent MOFs for gas sensing.